The Quest for Alternatives beyond (Neoliberal) Capitalism - Melisa R. Serrano; Edlira Xhafa (International Labour Organization (ILO), 2011)
Capitalism is not the only form of economy. Alternative economies - people's economies - exist in which human needs and relationships are more important than competition and profit. Forms of solidarity economy built on the principles and values of cooperation, equality, self-determination and democracy, exist and are taking shape in many parts of the world. These forms include household economies, barter economies, collective economies including cooperatives, worker-controlled economies, subsistence market economies, community budgeting, participatory budgeting, community-based local currency exchange systems, and ethical trading, among others. Labor organizations have also provided spaces for building capacities in the struggle to defy capitalism. The paper aims to contribute to the discourse on alternatives to capitalism. We go about by first examining recent works dealing with the issue of alternatives to capitalism (and neoliberalism). We define `alternative' as an on-going multidimensional, non-deterministic process of people's economic and political struggle beyond the capitalist logic, whether macro, meso or micro, to change their circumstances and simultaneously transform themselves in the process. Full development of human potential based on equality, solidarity and sustainability through democratic participatory processes is at the core of an alternative. Then, we look at how various forms of peoples' solidarity economies and state-initiated democratic participatory schemes become spaces or provide spaces for the development of counter-consciousness (outside the capitalist `common sense') and concomitantly build capacities for the development of projects, initiatives and economies beyond the capitalist logic. By addressing changes in the mode of production and the labor process within their spaces, we argue that many of these organizations, projects and initiatives, are the `materialization' or actual manifestation of non-capitalist alternatives. The first chapter provides an overview of recent discourses on possible alternatives to neoliberal globalization and capitalism. The second chapter looks at consciousness and counter-consciousness and how these processes relate to building capacities that enable the construction of `alternatives.' The third chapter analyses 13 selected cases (of peoples' solidarity economies, workers'/producers' cooperatives, alternative production systems and stateinitiated citizen democratic participation schemes) in terms of how they provide spaces for the development of counter-consciousness (outside the capitalist `common sense') and concomitantly capacities for the development of projects, initiatives and economies beyond capitalism. We also outline in this chapter the overall lessons and insights drawn from the case studies. Finally, in chapter four, we tie the main points underscored by literature we reviewed in chapter one, with the cases we analyzed in chapter three. We argue that the material practice of peoples' struggles fills the need for coherence on the alternatives to capitalism discourse. By bringing together and establishing a `dialogue' between theoretical debates and existing meso and micro social experiments and initiatives, we attempt to address the gap between macro level theoretical discourses and micro level practices. We argue that there are emancipatory and transformative elements that can be learned from people's practices and struggles, which allows for a more grounded framing of an alternative narrative beyond the capitalist logic. The chapter also recommends areas for further research.
Keywords: 330; capitalism; democracy; economy; globalization; economic theory